Effect of multidisciplinary health education based on lifestyle medicine on menopausal syndrome and lifestyle behaviors of menopausal women: A clinical controlled study - Li, Yangmei; He, Haiyang; Wang, Jiaxi; Chen, Yifan; Wang, Chunyuan; Li, Xinyue; Dai, Anqi; Liu, Yue; Xi, Xin; Huang, Juan; Zou, Mi; Fan, Yao; et al. (Frontiers in Public Health, 2023)
Objectives: This study aimed to evaluate the effect of multidisciplinary health education based on lifestyle medicine on menopausal syndrome and lifestyle behaviors of menopausal women. Methods: This study was designed as a clinical controlled trial in which intervention group (n=100) and control group (n=87) were matched for age, age at menarche, menopausal symptoms and drug use status at enrollment. Women in the intervention group received multidisciplinary health education based on lifestyle medicine for two months while those in the control group received routine outpatient health guidance. Menopausal syndrome, physical activity and dietary status of participants were assessed before and after the intervention. Results: Post intervention test indicated that menopausal syndrome of participants was significantly improved in the intervention group compared to the control group (P＜0.001). Between-group comparison showed a significantly improvement of weekly energy expenditure of total physical activity (P=0.001) and exercise physical activity (P0.001) in the intervention group compared to the control group after the intervention. The dietary status of participants was significantly improved in the intervention group compared to the control group (P0.001). In intervention group, the menopausal syndrome of participants has improved more in the hormone drug group than in the non-hormone group (P=0.007), as did the control group (P=0.024). In the hormone drug group, the physical activity (P=0.003) and dietary status (P=0.001) has improved more in the intervention group than in the control group. Conclusions: The multidisciplinary health education based on lifestyle medicine was proven to be effective in improving the menopausal syndrome and healthy lifestyle behaviors of menopausal women. Studies with extended observation period and larger size are in need to evaluate the long-term scale-up effects of the multidisciplinary health education.